2002
DOI: 10.1530/rep.0.1230217
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal environment, cytokines and angiogenesis in the pathophysiology of endometriosis

Abstract: Endometriosis, defined by the presence of viable endometrial tissue outside the uterine cavity, is a common condition affecting 2-3% of women of reproductive age. Today, a composite theory of retrograde menstruation with implantation of endometrial fragments in conjunction with peritoneal factors to stimulate cell growth is the most widely accepted explanation. There is substantial evidence that immunological factors and angiogenesis play a decisive role in the pathogenesis of endometriosis. In women with endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
197
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(208 citation statements)
references
References 17 publications
9
197
0
2
Order By: Relevance
“…Additionally, existing studies have documented instances of malignant transformation in endometriosis and malignancies arising from endometriosis, particularly ovarian cancers (25,26). Some studies have suggested that endometriotic lesions show resistance to apoptotic signals together with a capacity for unlimited replication, much like malignant tissues (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, existing studies have documented instances of malignant transformation in endometriosis and malignancies arising from endometriosis, particularly ovarian cancers (25,26). Some studies have suggested that endometriotic lesions show resistance to apoptotic signals together with a capacity for unlimited replication, much like malignant tissues (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Among the up-regulated factors, levels of monocyte chemotactic protein-1 (MCP-1), regulated on activation, normal T-cell expressed and secreted (RANTES) and VEGF are elevated by estrogen. 34 -37 To assess the contribution of FKBP52 deficiency to excessive estrogenic effects, concentrations of MCP-1, RANTES, and VEGF in mouse peritoneal fluid were measured by respective enzymelinked immunosorbent assay kits (R&D systems, Minneapolis, MN) according to the manufacturer's protocol.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…There is abundant evidence demonstrating that endometriosis is accompanied by inflammatory reactions in the peritoneum, resulting in abnormal levels of a variety of cytokines, chemokines and pro-inflammatory factors in the peritoneal fluid (Gazvani & Templeton, 2002;Lousse et al, 2010). It is also well known, that the number of macrophages is increased in the peritoneal fluid of endometriosis patients and that they are in a hyperactive state (Halme & Surrey, 1990;Raiter-Tenenbaum et al, 1998).…”
Section: Prostaglandins As Immune and Inflammatory Mediators In Endommentioning
confidence: 99%